2021
DOI: 10.3389/fnint.2021.662293
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Connectivity of the Human Paraventricular Thalamic Nucleus: Insights From High Field Functional MRI

Abstract: The paraventricular thalamic nucleus (PVT) is a small but highly connected nucleus of the dorsal midline thalamus. The PVT has garnered recent attention as a context-sensitive node within the thalamocortical arousal system that modulates state-dependent motivated behaviors. Once considered related to generalized arousal responses with non-specific impacts on behavior, accumulating evidence bolsters the contemporary view that discrete midline thalamic subnuclei belong to specialized corticolimbic and corticostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 102 publications
2
13
0
Order By: Relevance
“…The patient with a mildly significant decrease in perfusion in the bilateral thalamus and bilateral cerebellum on the 15 O-water PET did not show any abnormalities on their MRI perfusion image, which may indicate minor perfusion changes or nonspecific findings, although thalamus connectome data have suggested an association with anxiety. 15 , 16 However, the diffuse increase in perfusion in the cerebral white matter was observed on both the 15 O-water PET and MRI perfusion images. Previous studies have shown that increased cerebral blood volume and CBF can be detected in normal-appearing white matter in patients with inflammatory conditions, such as multiple sclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…The patient with a mildly significant decrease in perfusion in the bilateral thalamus and bilateral cerebellum on the 15 O-water PET did not show any abnormalities on their MRI perfusion image, which may indicate minor perfusion changes or nonspecific findings, although thalamus connectome data have suggested an association with anxiety. 15 , 16 However, the diffuse increase in perfusion in the cerebral white matter was observed on both the 15 O-water PET and MRI perfusion images. Previous studies have shown that increased cerebral blood volume and CBF can be detected in normal-appearing white matter in patients with inflammatory conditions, such as multiple sclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…To examine how PVT neurons undergo experience-dependent changes in gene expression, future investigations should include high throughput RNA-sequencing of the PVT following different biological conditions with the goal of comparing them with our atlas to identify potential biomarkers for therapeutic targeting. Indeed, based on the role of the rodent PVT in emotional processing and motivated behaviors, there is growing interest in the human PVT as a putative target for affective and substance abuse disorders, particularly since the human PVT has similar connectivity with the rodent PVT [132]. Excitingly, the existence of some markers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on delineating the circuitry of paraventricular thalamic nucleus (PVT), in view of its established and emerging roles in the encoding and integration of emotionally salient long-term memories (Do Monte et al, 2016;Kark et al, 2021;Kooiker et al, 2021) and the influence of these memories on behaviors during emotional conflicts (Choi et al, 2019). We assessed the impact of maternal grief on resting-state functional connectivity (RSFC) of the PVT.…”
Section: Resting State Functional Magnetic Resonance Imaging Analysismentioning
confidence: 99%
“…For one grief participant with a wider third ventricle width, the PVT seeds were slightly nudged away from x = 0 using MRICRON to fall on the paraventricular gray matter. This approach was based on our recently published work demonstrating the intrinsic structure and connectivity of the PVT in humans (Kark et al, 2021). Given the small size of the PVT and to address potential confounding effects of neighboring nuclei, we created a midline subnuclei control seed encompassing all midline nuclei using the Thalamus Atlas of the Swiss Federal Institute of Technology (ETH) in Zurich and University of Zurich, Switzerland (Krauth et al, 2010;Jakab et al, 2012).…”
Section: Resting State Functional Magnetic Resonance Imaging Analysismentioning
confidence: 99%
See 1 more Smart Citation